2016
DOI: 10.7763/ijcte.2016.v8.1054
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Opinion Mining in the Faculty Performance Evaluation System by the Students Using Naïve Bayes Algorithm

Abstract: Abstract-The paper promotes adoption of Opinion Mining in the faculty performance evaluation system by the students using Naï ve Bayes algorithm. The study may help the university administrators to identify the strengths and weaknesses of the faculty members based on the textual evaluation made by the students written either in English or in Filipino language. The system provides graphical representation of the evaluation result in pie chart with the percentage of positive and negative feedback of the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Attention to the value of user opinions made a great leap toward the approach of opinion mining and how it could enhance the web intelligence. Many researches used opinions from different points of views and in different fields as (Yuan et al, 2017) succeeded in using a sophisticated kind of opinions which is emotional features and social interactions to provide recommendations that meet user needs, ( Balahadia, & Comendador, 2016) depended on opinions in enhancing the performance and the level of services provided by a faculty and ( Jaskolski et al,2016) used opinion mining in predicting the relevant categories as well as the specific aspects in the field of distance education .…”
Section: Resultsmentioning
confidence: 99%
“…Attention to the value of user opinions made a great leap toward the approach of opinion mining and how it could enhance the web intelligence. Many researches used opinions from different points of views and in different fields as (Yuan et al, 2017) succeeded in using a sophisticated kind of opinions which is emotional features and social interactions to provide recommendations that meet user needs, ( Balahadia, & Comendador, 2016) depended on opinions in enhancing the performance and the level of services provided by a faculty and ( Jaskolski et al,2016) used opinion mining in predicting the relevant categories as well as the specific aspects in the field of distance education .…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that the model could effectively estimate online feedback. A crossbred attribute-centric sentiment categorization was introduced to incorporate domain-specific knowledge and extract definite word relations [13]. Datasets were created to test the effectiveness of the method.…”
Section: A Theories and Critical Reviewmentioning
confidence: 99%
“…The emotion classification approach affirmed by [12] is not efficient, as it uses only a lesser amount of data for analysis. The hybridized attribute-centric sentiment classification stated by [13] discovered the most prevalent bigrams and trigrams in the corpus. The method has proved unsuccessful in detecting the attribution and demanded a prolonged computational effort.…”
Section: B Gap Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a deeper understanding of the course that was not evident from quantitative data. Balahadia and Comendador (2016) performs opinion mining on students comment in Filipino or English, using Nave Bayes classifier. The results of the evaluation can be shown to higher management in the form of bar graphs and pie-charts.…”
Section: Usesmentioning
confidence: 99%